From avant-garde to negentropy : an aesthetic deployment of Bernard Stiegler's genealogy of the sensible - O'Dwyer, Néill (Trinity College (Dublin, Ireland). Department of Drama, 2016)
This thesis mobilises Bernard Stiegler’s call for a genealogy of the sensible in order to elucidate a peculiar phenomenon in art, which is the increase in the autonomy and efficacy of technology in the making and production of artwork. In doing so, the thesis follows a historical trajectory that considers works by Marcel Duchamp, John Cage, Samuel Beckett, Klaus Obermaier, Chunky Moves and Driessens and Verstappen. These artists have been selected because it is held that their works are quintessentially avant-garde in their nature. Of particular interest to this study is the fact that each of their works engages artistic production in a systematic way, at the nexus of chance operations and new technologies / techniques. The main analytical methodology that is used for examining these works is the aesthetic theory of Bernard Stiegler, a contemporary French philosopher working in the tradition of continental philosophy. Stiegler’s main interest is the philosophy of technology, which he analyses using a synthesis of theories of individuation, anthropology, phenomenology and cultural critique. This gives rise to an aesthetic argumentation that is deeply cogitative on the overlapping sectors of the philosophical, historical-material and political domains. The purpose of this genealogical investigation is to show, on the one hand, that historical avant-garde strategies of investigating the thematics of indeterminacy via new technologies are still useful and effective in the contemporary digitalised world, and on the other hand, that the resulting ‘chance’ inventions are reflective of a more general, societal inclination towards fabricating increasingly naturalistic, autonomous agents that display quasi-organic characteristics. By tracing the increasing use of ‘automatisation’ in the generation of aleatoric, avant-garde artworks, this thesis elucidates parallels between the increasing agency of machines and the (in)determinate efficacy they hold over humans, in both art and broader sociological processes. In this way, for Stiegler, avant-garde creative endeavours are treated as cutting-edge experiments where the relational boundaries between technology and the mental / physical self are undermined, fragmented, reconfigured and at times completely obliterated. The philosophy of Stiegler is employed in order to reflect on how the objects of discussion are considered precursors of a more general sociopolitical and economic trajectory towards generalised and pervasive processes of automatisation. As such, the thesis asks how artists, and the general public, can respond to the increased pressures and mutated subjectivities brought to bear by the ubiquity of the digital. The thesis concludes by contending that the avant-garde’s exploratory methodology and praxis is the domain where these questions can be best engaged, because it still maintains the power to ameliorate ‘a people’ (Deleuze, 2005, 209) by forging new realities through the experimental reinvention and repurposing of artefacts.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin